Social potential in spatial organization and urban development in terms of forming of informational society - Gabrel, Mykola; Khromyak, Josef; Lysyak, Nataliya (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
This article investigates the relationship between the social potential of city and the architecture and town-planning organization. As such the problem of public potential for urban planning tasks was analyzed on theoretical basis and research methods were selected. The social characteristics of Lwow were identified in the light of the city objective and subjective properties. An association between the social potential and the spatial potential was identified. A justification of the ways in which spatial changes are based on the requirements of structuralization and the effective use of public potential.

W artykule przedstawiono relacje występujące między potencjałem społecznym miasta a jego architekturą i organizacją urbanistyczną. Problem znaczenia potencjału społecznego w zagadnieniach planowania urbanistycznego przedstawiono w ujęciu teoretycznym i dokonano wyboru metod badania. Scharakteryzowano społeczny potencjał Lwowa z uwzględnieniem jego obiektywnych i subiektywnych właściwości. Wskazano na powiązania występujące między potencjałem społecznym a obszarem oraz przedstawiono przestrzenną lokalizację tego potencjału. Uzasadniono kierunki przestrzennych zmian na podstawie wymagań strukturalizacji i skutecznego wykorzystania społecznego potencjału.